Exogenous leucine alleviates heat stress and improves saponin synthesis in Panax notoginseng by improving antioxidant capacity and maintaining metabolic homeostasis - Liu, Haijiao; Su, Yingwei; Fan, Yunxia; Zuo, Denghong; Xu, Jie; Liu, Yixiang; Mei, Xinyue; Huang, Huichuan; Yang, Min; Zhu, Shusheng (Frontiers in Plant Science, 2023)
Panax notoginseng saponins (PNSs) are used as industrial raw materials to produce many drugs to treat cardio-cerebrovascular diseases. However, it is a heat-sensitive plant, and its large-scale artificial cultivation is impeded by high temperature stress, leading to decreases in productivity and PNSs yield. Here, we examined exogenous foliar leucine to alleviate heat stress and explored the underlying mechanism using metabolomics. The results indicated that 3 and 5 mM exogenous foliar leucine significantly alleviated heat stress in one-year- and two-year-old P. notoginseng in pots and field trials. Exogenous foliar leucine enhanced the antioxidant capacity by increasing the activities of antioxidant enzymes (POD, SOD) and the contents of antioxidant metabolites (amino acids). Moreover, exogenous foliar leucine enhanced carbohydrate metabolism, including sugars (sucrose, maltose) and TCA cycle metabolites (citric acid, aconitic acid, succinic acid and fumaric acid), in P. notoginseng leaves, stems, and fibrous roots to improve the energy supply of plants and further alleviate heat stress. Field experiments further verified that exogenous foliar leucine increased the productivity and PNSs accumulation in P. notoginseng. These results suggest that leucine application is beneficial for improving the growth and quality P. notoginseng under heat stress. It is therefore possible to develop plant growth regulators based on leucine to improve the heat resistance of P. notoginseng and other crops.